THE LEGAL PROTECTION FOR APPRENTICES IN INDONESIA - Nizam Zakka Arrizal; Lanny Ramli (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study observes about the legal protection for apprentice in the country. This research uses normative juridical method. The result of the study shows that an apprenticeship is categorized into the dispute of interest. In the aspect of apprenticeship, several legal remedies are known if a dispute arises: through litigation or non-litigation which are detailed as Meditation (Peace), Bipartite Negotiation Institution, Conciliation, Arbitration, and through the Industrial Relations Court.To provide a normative study of legal protection for apprentice in the country, identify legal loophole in the legislation, and discover what legal remedy that apprentices can do if their rights are violated by the employer.The recipient company often uses the "nescience" of apprentices to work in equal portions as well as a long period of time just like the permanent employees. However, the wages are not proportional with the work delegated to the apprentices.